1990
DOI: 10.1002/ccd.1810210110
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery anomalies in 126,595 patients undergoing coronary arteriography

Abstract: Coronary artery anomalies were found in 1,686 patients (1.3% incidence) undergoing coronary arteriography at the Cleveland Clinic Foundation from 1960 to 1988. Of the 1,686 patients, 1,461 (87%) had anomalies of origin and distribution, and 225 (13%) had coronary artery fistulae. Most coronary anomalies did not result in signs, symptoms, or complications, and usually were discovered as incidental findings at the time of catheterization. Eighty-one percent were "benign" anomalies: 1) separate origin of the left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

64
1,659
18
69

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,865 publications
(1,810 citation statements)
references
References 53 publications
64
1,659
18
69
Order By: Relevance
“…This was compatible with the Lipton L1 classification of single coronary artery anomalies (1). The absence of the RCA ostium originating as a continuation of the distal left circumflex artery is extremely rare, with an incidence of 0% to 0.035% (2). Such an anomaly is not expected to cause ischemia or any other complication.…”
supporting
confidence: 85%
“…This was compatible with the Lipton L1 classification of single coronary artery anomalies (1). The absence of the RCA ostium originating as a continuation of the distal left circumflex artery is extremely rare, with an incidence of 0% to 0.035% (2). Such an anomaly is not expected to cause ischemia or any other complication.…”
supporting
confidence: 85%
“…Congenital anomalous origin of the coronary arteries may not be uncommon [2]. Angelini [3] reported that it might occur in 1-1.2 % of all coronary angiograms performed, with 0.15 % incidence of anomalous origination of the left coronary artery from the right sinus as that of the present case.…”
Section: Importance Of Awareness Of Congenital Coronary Anomalies Forsupporting
confidence: 49%
“…[10][11][12] Malignant anomalies may have serious implications such as angina pectoris, myocardial infarction, syncope, cardiac arrhythmias, congestive heart failure, or sudden death. 13 Especially in the young, coronary anomalies are an important cause of sport-related sudden cardiac death. Coronary anomalies rank second as a cardiovascular cause of sudden death in the young behind hypertrophic cardiomyopathy.…”
Section: Coronary Artery Anomaliesmentioning
confidence: 99%